The Effect of Coffee Arabica (Coffea arabica L.) Fruit Skin Extracts on Small Intestine Morphometry of mice (Mus musculus L.) with Ethanol-Induced - Rita Maliza; Febriofca Galih Yatalaththov; Haris Setiawan; Listiatie Budi Utami (Bioscience, 2021)
Consumption of alcoholic beverages can increase ROS and inflammation. In the duodenal, the consumption of alcohol can result in erosions, bleeding, and mucosal injury. Arabica coffee fruit skin contains antioxidant substances, which are expected to have a good role as an antioxidant effect. Currently, unknown effects of alcohol and extract of Arabica coffee fruit skin administration on the damage of the small intestine of mice (Mus musculus L.). This study used an experimental design, and 25 males of mice were divided into five groups of treatment for 15 days. After the treatment, the mice at necropsied and the small intestine were taken for histopathological examination using hematoxyline-eosin staining. The Data analyzed used One Way ANOVA and Duncan's tests. Histopathological observations showed a dose of 250 mg/kg BW experienced the most significant improvement damage of the small intestine of mice compared to other treatments. Histomorphometry measurement, The dose of 250 mg/kg BB showed the high of villi 272,10 ± 13,36 µm, (P<0.05), duodenal villi crypt depth 117,33 ± 30,35 µm (P<0.05) and surface area of small intestinal villi 7,66 ± 0,55 mm2 (P<0.05) was similar with negative control. The conclusion of this study is a dose of 250 mg/kg BW treatment was able to improve the histopathology and morphometry small intestine of mice that were damaged due to consumption of ethanol 15%.